Multifactorial influences on musical creativity: an integrated perspective on cognitive and social capital factors - Ben, Shaohua; Zheng, Wenjun; Li, Xu (Frontiers in Psychology, 2025)
IntroductionMusical creativity is a crucial aspect of music education and innovation. This study has aimed to systematically examine its key determinants, with particular attention to cognitive and social capital mechanisms.MethodsGrounded in the componential theory of creativity, social capital theory, social cognitive theory, this study has developed a conceptual framework incorporating five explanatory variables. It has employed partial least squares structural equation modeling (PLS-SEM) to analyze data from 962 university students.ResultsThe findings have revealed that social capital has exerted both direct effect and moderating effect on creative self-efficacy. While creative thinking has emerged as the strongest antecedent, its influence on musical creativity has diminished under the moderation of social capital. In contrast, musical aesthetic ability, though the weakest antecedent, has demonstrated a significant effect on musical creativity when moderated by social capital. Furthermore, creative self-efficacy has served as a mediating factor in the musical creativity model.ConclusionThis study has highlighted the complex interplay between cognitive and social capital in shaping musical creativity, thereby enriching its theoretical foundation. The findings have offered novel insights and practical implications for music education by equipping educators with strategies to cultivate students' creative potential and encourage innovation in higher education.